A Digital Watermarking Algorithm Based on Wavelet Packet Transform and RBF Neural Network - Saxena, Poorvi; Vishwakarma, Murlidhar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Digital water marking technique suffered some problem of geometrical and some other attack. The process of attack deformed the quality of digital image and violet the rule of copyright protection low. For the roughness of digital image watermarking used wavelet transform function and RBF neural network. The RBF neural network trained the pattern of digital image pixel and finally embedded the image. The processes of validation of blindness of digital image apply some geometrical attack. Our empirical result computed in form of PSNR value and number of correlation of embedded image. Our evolution process shows better result in compression of transform based digital water marking technique.